Prarancangan Pabrik Sodium Dodekilbenzena Sulfonat dari Dodekilbenzena dan Oleum 20% Kapasitas 50.000 Ton/Tahun - Saputra, Harjuna Mukti, Ir. Nur Hidayati, M.T., Ph.D, Kun Harismah, Ph.D (2016)
Pre-design of sodium dodecylbenzene sulfonates plant is intended to meet the requirement of sodium dodecylbenzene sulfonates in the country and overseas. Sodium dodecylbenzene sulfonates is made by sulfonation dodecylbenzene reaction with oleum 20%. The production process of sodium dodecylbenzene sulfonates is performed in the reactor continous stirred tank reactor. The use of sodium dodecylbenzene sulfonates is for in the production of synthetic detergents, and washing the car shampoo. Location of sodium dodecylbenzene sulfonates plant is planned in the industrial zones established in Cilegon, Banten. The selected production process is the sulfonation process that use 20% oleum because of lower cost, easy handling, and higher conversion. The reaction takes place in the liquid phase, at temperature of 46°C and a pressure of 1 atm. Dodecylbenzene sulfonates sodium plant with a capacity of 50,000 tons per year requires raw materials as many as 39,929.7 tons oleum per year, 32,397.3 tons dodecylbenzene per year and 5,676.6 tons NaOH per year. The utility need 48,159.6 tons water per year, 11,969.781 litres fuel per year, and 288.6766 kW electricity. The water process is provided by largest river in Cilegon, it is Grogol river. Economic analysis conclude that Percent Return On Investment (ROI) of 44.14% before tax and 30.90% after tax. Pay Out Time (POT) before tax is 1.85 years and that of after tax is 2.45 years. Break Even Point (BEP) is 44.23%, and Shut Down Point (SDP) is 25.37%. Internal Rate of Return (IRR) is 41.86%. Based on the data above, the plant of sodium dodecylbenzene sulfonates possible to set up.